Mobile health: the power of wearables, sensors, and apps to transform clinical trials. Issue 1 (6th July 2016) - Munos, Bernard; Baker, Pamela C.; Bot, Brian M.; Crouthamel, Michelle; de Vries, Glen; Ferguson, Ian; Hixson, John D.; Malek, Linda A.; Mastrototaro, John J.; Misra, Veena; Ozcan, Aydogan; Sacks, Leonard; et al.
Abstract : Mobile technology has become a ubiquitous part of everyday life, and the practical utility of mobile devices for improving human health is only now being realized. Wireless medical sensors, or mobile biosensors, are one such technology that is allowing the accumulation of real‐time biometric data that may hold valuable clues for treating even some of the most devastating human diseases. From wearable gadgets to sophisticated implantable medical devices, the information retrieved from mobile technology has the potential to revolutionize how clinical research is conducted and how disease therapies are delivered in the coming years. Encompassing the fields of science and engineering, analytics, health care, business, and government, this report explores the promise that wearable biosensors, along with integrated mobile apps, hold for improving the quality of patient care and clinical outcomes. The discussion focuses on groundbreaking device innovation, data optimization and validation, commercial platform integration, clinical implementation and regulation, and the broad societal implications of using mobile health technologies.